EFFECTIVENESS OF RENEWABLE ENERGY LAMPS ON GATHERING FISH IN BAGAN FISHERIES AT BANTEN BAY - Dirfas Heronseva Sudrajad; Atsuhiro Tsunoda; Mulyono Sumitro Baskoro; Mohammad Imron (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
The increase in solar fuel (diesel) prices poses major challenge for lift net (bagan) fishermen who rely on generators for their fish-attracting lights. This research investigates the effectiveness of the innovative EBT Lamp (Lacuba) powered by a Seawater Battery as an alternative to solar-fueled generators. The primary objective is to evaluate the performance of Lacuba, focusing on the speed of fish attraction and aggregation, as well as the analysis of community indices (diversity, evenness, and dominance) of the catches. Field trial results indicate that Lacuba is significantly more time-efficient. The average time for fish to be attracted was 6.5 minutes (vs. 12.25 minutes with conventional lamps), and the aggregation time was 60 minutes (vs. 77 minutes). Although both systems showed low community index categories, Lacuba registered lower values for diversity (0.2965), evenness (0.1842), and dominance (0.0392) compared to the conventional fishing lamp. Key words: lift net, renewable energi, seawater battery